PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS II SDN 105344 DENAI LAMA - Irawati Panjaitan; Umar Darwis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The objective of this research was to determine whether the Picture and Picture learning model influences the beginning reading skills of Grade II students at SDN 105344 Denai Lama. This research employed a quasi-experimental method with a pretest-posttest control group design. The research results show that the experimental class, which used the Picture and Picture learning model, had an average score of 86.1, while the control class, which used the conventional model, had an average score of 78.4. The difference in reading ability between the experimental and control classes was analyzed using a T-test with SPSS version 29, yielding a significance value (????) < 0.05, specifically 0.003 and 0.004, indicating that Ha was accepted and H0 was rejected. Additionally, T_observed > T_table (3.115 > 2.02439), confirming that there was a significant difference in reading skills between students taught using the Picture and Picture model and those taught using conventional methods. Effectiveness of the Picture and Picture Model: The Picture and Picture model was proven effective in enhancing students' reading skills by fostering active engagement and increasing interest through visually presented materials. This method helped students understand reading contexts, expand vocabulary, and accelerate comprehension. Findings and Limitations: Although this research supports the effectiveness of the Picture and Picture model in improving students' reading skills, certain limitations, such as a short research duration and focus on a single dependent variable, suggest the need for further studies involving a more diverse population and a longer research period. Overall, this research concludes that the Picture and Picture learning model is an effective method for improving early-grade students' reading skills. Therefore, it can serve as an alternative teaching method to enhance students' literacy skills in schools.